ZIKV infection induces robust Th1-like Tfh cell and long-term protective antibody responses in immunocompetent mice - Huabin Liang (Nature Portfolio, 2019)
Here, the authors show that Zika virus (ZIKV) infection induces Th1-like Tfh cells that depend on T-bet for their development and are essential for class switching of ZIKV-specific IgG2c antibodies and maintenance of long-term neutralizing antibody responses.